0699 Daytime Physical Activity and Subsequent Changes in Sleep in Older Men: The MrOS Study. (27th April 2018) - Li, J; Blackwell, T; McPhillips, M; Smagula, S F; Pack, A; Ancoli-Israe, S; Gooneratne, N; Stone, K
Abstract: Introduction: Limited daytime physical activity may impact nocturnal sleep in older adults. In addition to the amount of daytime physical activity, the timing of activity may also play a role in night-time sleep. To inform strategies for preventing sleep problems in older adults, we sought to identify which aspects of activity (e.g., timing or amount) were related to changes in nocturnal sleep among older men over a six-year period. Methods: A total of 988 community-dwelling men aged 67 and older wore wrist actigraphs and completed in-home polysomnography (PSG) in 2002–04 (baseline) and 2009–11, as participants in the Osteoporotic Fractures in Men Study (MrOS) Sleep ancillary study. Physical activity at baseline was assessed using activity count per minute from actigraphy. Morning, afternoon, and evening physical activity were defined as average activity from rise time to noon, noon to 4pm, and 4pm till bedtime, respectively. Primary sleep measures included sleep efficiency (SE) from actigraphy and slow wave sleep (SWS) from PSG. Changes in sleep (follow-up minus baseline scores) were analyzed both continuously (per 100-unit activity increase) and dichotomously (lowest quartile vs three other quartiles). Results: Higher overall daytime physical activity (β=0.15, p<0.01), morning activity (β=0.14, p=0.01) and evening activity (β=0.13, p<0.01) were associated with slower decline in SE from baseline to follow-up; these associations were independent of study site, age, race, education, body mass index, depression, comorbidities, self-reported health status, smoking, drinking, benzodiazepine and antidepressant use, and cognitive function. Higher afternoon activity was associated with worse changes in SE (β=-0.10, p<0.04). People in the lowest quartile of overall physical activity had 61% increased risk of being in the worst quartile of SE change (p<0.03). No significant association was found between daytime activity measures and change in SWS. Conclusion: Physical activity reduced the decline between baseline and over 6 years in SE, but not SWS. Being active in general, especially in the morning and the evening, was beneficial for older adults to sustain/ improve sleep. Support (If Any): K99NR016484, U01AR45614, U01AR45632, U01AR45647, U01AR45654, U01AR45583, U01AG18197, U01AG027810, and UL1RR024140.